Risk Factors of Dengue Hemorrhagic Fever in Oesapa Village, Kelapa Lima Sub-District - Maria A. L. Kelen; Johny A. R. Salmun; Agus Setyobudi (Media Kesehatan Masyarakat, 2022)
DHF can cause illness and death. The number of DHF at the Oesapa Health Center tends to fluctuate, with 60 cases in 2016, 25 cases in 2017 and 55 cases in 2018. There were 60 dengue cases in 2019 (until April 2019) (IR:0,41/100.000 people) and there was an outbreak (KLB). The aim of this study was to determine the risk factors for dengue fever with dengue outbreaks in 2019 in the village of Oesapa, Kelapa Lima district, Kupang city. This type of research is analytical observation with a case control design. The sample in this study consisted of 100 respondents, consisting of 50 case respondents and 50 control respondents using a simple random sampling technique and the data were analyzed using the chi-square analysis. The study shows that the risk factors for dengue fever in Oesapa Village, Kelapa Lima District, Kupang City are the eradication of mosquito nets (ρ=0.001), occupancy density (ρ=0.045), the presence of larvae (ρ=0.026). The community is expected to maintain and protect individual health and the environment, especially 3M Plus measures to avoid the risk of dengue fever.